Fireproof flame-retardant rubber connecting piece and preparation method thereof

Through the combination of phosphorus-nitrogen composite flame retardant and ultrafine carbon materials, the problems of flammable and harmful substance release of rubber connectors at high temperatures are solved, and efficient and environmentally friendly flame retardant performance and production efficiency are improved.

CN120310080APending Publication Date: 2025-07-15YANGZHOU RUNFA RUBBER & PLASTIC CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510453763.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

Existing fire-resistant and flame-retardant rubber connectors are flammable at high temperatures, release harmful substances, affect the environment and health, and have low production efficiency.

Method used

Rubber connectors are prepared through segmented mixing and molded vulcanization to improve flame retardant performance and fluidity.

Benefits of technology

Improves the flame retardant performance and safety of rubber connectors, reduces the release of harmful substances, and reduces production costs and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120310080A_ABST
    Figure CN120310080A_ABST
Patent Text Reader

Abstract

The invention discloses a fireproof flame-retardant rubber connecting piece and a preparation method thereof. The fireproof flame-retardant rubber connecting piece comprises the following components in parts by weight: 90-100 parts of nitrile rubber, 20-30 parts of aluminum hydroxide, 10-15 parts of brucite powder, 10-12 parts of a phosphorus-nitrogen composite flame retardant, 2-5 parts of zinc borate, 10-20 parts of carbon black, 3-6 parts of a vulcanization system, 1-2 parts of a processing aid, 1-3 parts of a superfine carbon material and 1-2 parts of tea polyphenol. The phosphorus-nitrogen composite flame retardant and the superfine carbon material are introduced, so that the oxygen index and the UL94 vertical combustion grade of the rubber connecting piece are improved, the fire risk is reduced, and the safety is enhanced; by selecting and adding a processing aid, such as stearic acid, the flowability and mixing uniformity of the material are improved, the equipment wear is reduced, the production time and cost are reduced, and the production efficiency is improved; the natural plant extract and the phosphorus-nitrogen composite flame retardant are adopted, so that the release of harmful substances is reduced while the flame retardant property is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of rubber production, and particularly to a fireproof and flame-retardant rubber connector and a preparation method thereof. Background Technique

[0002] In the prior art, fireproof and flame-retardant rubber connectors are widely used in fields such as construction, electricity, and transportation, mainly to enhance the safety of materials in high-temperature and fire situations. Traditional rubber materials are easily combustible in high-temperature environments and produce harmful gases. Therefore, there is an urgent need to develop rubber connectors with excellent fireproof and flame-retardant properties. Existing flame-retardant technologies mainly include physical flame retardancy and chemical flame retardancy. Physical flame retardancy is achieved by increasing the material thickness and fireproof coatings, while chemical flame retardancy reduces the combustion performance by adding flame retardants. Common flame retardants such as aluminum hydroxide, phosphates, and halogens, etc., but these materials may release toxic gases at high temperatures, posing potential threats to the environment and health. In recent years, researchers have begun to focus on the development of new environmentally friendly flame retardants, such as bio-based flame retardants and nanomaterials, in order to improve the environmental characteristics of materials while maintaining the flame-retardant performance. In short, the research and development of fireproof and flame-retardant rubber connectors are moving towards the direction of green, safe, and high-performance to meet the growing market demand.

[0003] However, there are still great deficiencies in the prior art, such as:

[0004] In the prior art: Traditional rubber materials are flammable in high temperature and flames, resulting in major safety hazards during the use of products. After adding flame retardants and other functional materials, the fluidity and processing performance of rubber decline, leading to low production efficiency and increased production costs. Some traditional flame retardants or fillers may release harmful substances during use, affecting the environment and human health. Summary of the Invention

[0005] The purpose of the present invention is to provide a fireproof and flame-retardant rubber connector and a preparation method thereof to solve the problems raised in the above background technique.

[0006] To achieve the above purpose, the present invention provides the following technical solutions:

[0007] A fireproof and flame-retardant rubber connector includes the following components in parts by weight: 90 - 100 parts of nitrile rubber, 20 - 30 parts of aluminum hydroxide, 10 - 15 parts of brucite powder, 10 - 12 parts of phosphorus-nitrogen compound flame retardant, 2 - 5 parts of zinc borate, 10 - 20 parts of carbon black, 3 - 6 parts of vulcanization system, 1 - 2 parts of processing aids, 1 - 3 parts of ultrafine carbon material, and 1 - 2 parts of tea polyphenols.

[0008] Preferably, the phosphorus-nitrogen compound flame retardant is a compound of ammonium polyphosphate and melamine polyphosphate, and the mass ratio of ammonium polyphosphate to melamine polyphosphate is 2:1.

[0009] Preferably, the brucite powder is surface-modified with a silane coupling agent KH-550, and the addition amount of the modifier is 1-3% of the mass of the brucite powder.

[0010] Preferably, the vulcanization system consists of sulfur, zinc oxide and accelerator DM, and the mass ratio of sulfur, zinc oxide and accelerator DM is 2:5:2.

[0011] Preferably, the diameter of the zinc borate particles is less than 5 microns, the super-new carbon material is graphene, and the processing aid is stearic acid.

[0012] A preparation method of a fireproof and flame-retardant rubber connector includes the following steps:

[0013] Pretreatment: Under the condition of 80-100 °C, 15 parts of brucite powder are mixed with 1.5 parts of silane coupling agent KH-550, and high-speed stirring is used for mixing for 20 minutes to ensure that the silane is evenly coated on the surface of the brucite powder to improve its compatibility with the rubber matrix;

[0014] Pre-dispersion: Weigh 6 parts of ammonium polyphosphate and 6 parts of melamine polyphosphate, and ball-mill them in a ball mill to ensure that their particle size is less than 5 μm. After the ball-milling is completed, 5 parts of zinc borate are added to the mixture, and ball-milling is continued until fully mixed to form a uniform composite particle, which is made into a slurry with liquid paraffin according to a mass ratio of 1:0.5;

[0015] Segmented mixing: The first stage: NBR is plastically refined in a mixer at 120-125 °C for 2-4 minutes;

[0016] The second stage: Add 50-60% of the phosphorus-nitrogen composite flame retardant and carbon black, and mix at 130-140 °C for 4-6 minutes;

[0017] The third stage: Add the remaining raw materials and mix at 120-130 °C for 3-5 minutes;

[0018] Vulcanization and molding: The mixed rubber is molded and vulcanized under pressure of 150-165 °C and 12-18 MPa, and the vulcanization time is calculated at 1.2-1.8 minutes per millimeter of the product thickness.

[0019] Preferably, during the segmented mixing process, the mixing temperature in the second stage is 5-15 °C higher than that in the third stage.

[0020] Preferably, during the third stage of segmented mixing, a smoke suppressant accounting for 0.5-1.5% of the total mass of the rubber is added, and the smoke suppressant is a compound of ferrocene and ammonium molybdate with a mass ratio of (2:1)-(1:1).

[0021] Preferably, the vulcanization time is calculated at 1.5 minutes per millimeter of the product thickness.

[0022] Preferably, the smoke suppressant is a composite of ferrocene and ammonium molybdate, and the mass ratio is 2:1.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0024] 1. By introducing a phosphorus-nitrogen composite flame retardant and ultrafine carbon material, the oxygen index and UL94 vertical burning grade of the rubber connector are improved, the fire risk is reduced, and the safety is enhanced.

[0025] 2. By selecting and adding processing aids, such as stearic acid, the fluidity and mixing uniformity of the material are improved, equipment wear is reduced, production time and cost are reduced, and production efficiency is increased.

[0026] 3. By using natural plant extracts and phosphorus-nitrogen composite flame retardants, the release of harmful substances is reduced while ensuring the flame retardant performance. Description of the Drawings

[0027] Figure 1 It is a comparison table of the formula contents of Example 1 and Example 2 of the present invention. Detailed Embodiments

[0028] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0029] Please refer to Figure 1 , the present invention provides a technical solution:

[0030] A fireproof and flame-retardant rubber connector includes the following components in parts by weight: 90-100 parts of nitrile rubber, 20-30 parts of aluminum hydroxide, 10-15 parts of brucite powder, 10-12 parts of phosphorus-nitrogen composite flame retardant, 2-5 parts of zinc borate, 10-20 parts of carbon black, 3-6 parts of vulcanization system, 1-2 parts of processing aid, 1-3 parts of ultrafine carbon material, and 1-2 parts of tea polyphenols.

[0031] Nitrile rubber is used as the matrix material to provide good mechanical properties, oil resistance and wear resistance. Aluminum hydroxide is used as an inorganic flame retardant, which can release water at high temperatures, reduce the flame temperature, and form a protective layer to slow down the burning speed.

[0032] The phosphorus-nitrogen composite flame retardant is a composite of ammonium polyphosphate and melamine polyphosphate, and the mass ratio of ammonium polyphosphate to melamine polyphosphate is 2:1.

[0033] The phosphorus-nitrogen compound flame retardant, as a synergistic flame retardant component, inhibits flame spread by releasing phosphoric acid and ammonia, forms a charred layer to isolate oxygen, enabling the rubber material to have better flame retardancy. Zinc borate, as a smoke suppressant aid, suppresses smoke synergistically with halogens and reduces the generation amount of carbon monoxide;

[0034] The brucite powder is surface-modified, with the modifier being silane coupling agent KH-550, and the addition amount of the modifier being 1-3% of the mass of the brucite powder.

[0035] By using the modified brucite powder to replace part of aluminum hydroxide, it absorbs heat during decomposition at 380°C, forms a dense magnesium oxide layer to isolate oxygen, further improves the flame retardant effect, and is also used as an auxiliary flame retardant, enhancing the strength and wear resistance of carbon black-reinforced materials. Processing aids such as stearic acid can improve the mixing and processing performance, reduce friction, enhance the fluidity and mixing uniformity of the material, ensuring that the fluidity and processability of the rubber can still be guaranteed after adding the flame retardant and other functional materials; Ultra-fine carbon materials such as graphene can improve the electrical conductivity and mechanical strength of the material and synergistically enhance the flame retardancy. Tea polyphenols have excellent antioxidant properties, can further improve the heat resistance and flame retardancy of the material, and are more environmentally friendly as natural extracts;

[0036] The vulcanization system consists of sulfur, zinc oxide and accelerator DM, and the mass ratio of sulfur, zinc oxide and accelerator DM is 2:5:2.

[0037] The vulcanization system is used for the cross-linking of rubber, improving the heat resistance, physical properties and service life of the material.

[0038] The particle diameter of zinc borate is less than 5 microns, the ultra-fine carbon material is graphene, and the processing aid is stearic acid.

[0039] A preparation method of a fireproof and flame-retardant rubber connector, which is characterized by including the following steps:

[0040] Pretreatment: Under the condition of 80-100°C, mix 15 parts of brucite powder with 1.5 parts of silane coupling agent KH-550, and mix them by high-speed stirring for 20 minutes to ensure that the silane is evenly coated on the surface of the brucite powder to improve its compatibility with the rubber matrix;

[0041] Prepare all the required raw materials, ensure the amount of each component is accurate to meet the formula requirements, weigh each component using a precision balance, place them in clearly marked containers respectively, record the weight of each component, and then perform surface modification treatment on the brucite powder. Put 15 parts of brucite powder and 1.5 parts of silane coupling agent KH-550 into a high-temperature stirrer, set the temperature of the stirrer to 90°C, and stir at high speed for 15 minutes to ensure that the silane is evenly coated on the surface of the brucite powder. Take out the modified brucite powder and place it in a well-ventilated place to cool;

[0042] Then, prepare the phosphorus-nitrogen composite flame retardant. Weigh 6 parts of ammonium polyphosphate and 6 parts of melamine polyphosphate, put them into a ball mill, and carry out ball milling to ensure that their particle size is less than 5 μm. The ball milling time is 30 minutes. After the ball milling is completed, add 5 parts of zinc borate to the mixture and continue ball milling for 10 minutes to ensure thorough mixing;

[0043] Pre-dispersion: Weigh 6 parts of ammonium polyphosphate and 6 parts of melamine polyphosphate, carry out ball milling in a ball mill to ensure that their particle size is less than 5 μm. After the ball milling is completed, add 5 parts of zinc borate to the mixture and continue ball milling until thorough mixing to form uniform composite particles, and make a slurry with liquid paraffin according to a mass ratio of 1:0.5;

[0044] Prepare a clean mixing container, add 100 ml of light mineral oil or liquid paraffin as a solvent, add the prepared phosphorus-nitrogen composite flame retardant and zinc borate mixture into the container, and use a stirrer to stir at medium speed for 5 minutes until the slurry is uniform;

[0045] Staged mixing: First stage: Plasticate the nitrile rubber in an internal mixer at 120 - 125 °C for 2 - 4 minutes;

[0046] Second stage: Add 50 - 60% of the phosphorus-nitrogen composite flame retardant and carbon black, and mix at 130 - 140 °C for 4 - 6 minutes;

[0047] Third stage: Add the remaining raw materials and mix at 120 - 130 °C for 3 - 5 minutes;

[0048] Vulcanization and molding: Mold and vulcanize the mixed rubber at 150 - 165 °C and a pressure of 12 - 18 MPa. The vulcanization time is calculated at 1.2 - 1.8 minutes per millimeter of the product thickness.

[0049] During the staged mixing process, the mixing temperature in the second stage is 5 - 15 °C higher than that in the third stage.

[0050] Add a smoke suppressant accounting for 0.5 - 1.5% of the total mass of the rubber in the third stage of the staged mixing. The smoke suppressant is a compound of ferrocene and ammonium molybdate with a mass ratio of (2:1) - (1:1).

[0051] The vulcanization time is calculated at 1.5 minutes per millimeter of the product thickness.

[0052] The smoke suppressant is a compound of ferrocene and ammonium molybdate with a mass ratio of 2:1.

[0053] Put 100 parts of nitrile rubber into an internal mixer, set the temperature at 120 - 125 °C, and plasticate for 2 - 4 minutes until the rubber reaches a good plastic state. Add a total of 50 - 60% of the slurry of the phosphorus-nitrogen composite flame retardant and zinc borate to the internal mixer, adjust the temperature to 135 °C, and continue mixing for 4 - 6 minutes to ensure uniform dispersion of the raw materials,

[0054] Then, add 30 parts of aluminum hydroxide and 15 parts of surface-modified brucite powder. Add the remaining 3 parts of ultra-fine carbon material, 1.5 parts of natural plant extract, and 2 parts of processing aid into a kneader, control the temperature at 120 - 130 °C, and knead for 3 - 5 minutes to ensure that all components are fully and evenly mixed. Add a smoke suppressant accounting for 0.5 - 1.5% of the total mass of the rubber in the third stage of staged kneading;

[0055] Then, carry out vulcanization molding. Transfer the kneaded rubber compound to a mold, ensure that the mold is clean and dry, set the molding temperature at 150 - 165 °C, apply a pressure of 12 - 18 MPa for molding, and calculate the vulcanization time according to the thickness of the product, which is 1.5 minutes per millimeter. For example, if the product thickness is 3 mm, the vulcanization time is 4.5 - 5.4 minutes. After vulcanization is completed, quickly take out the mold and cool it.

[0056] Example 1: Formula:

[0057] Nitrile rubber: 100 parts

[0058] Aluminum hydroxide: 25 parts

[0059] Brucite powder: 12 parts

[0060] Phosphorus-nitrogen compound flame retardant: 11 parts (mass ratio of ammonium polyphosphate to melamine polyphosphate is 2:1)

[0061] Zinc borate: 4 parts (particle diameter less than 5 microns)

[0062] Carbon black: 15 parts

[0063] Vulcanization system: 5 parts (mass ratio of sulfur, zinc oxide to accelerator DM is 2:5:2)

[0064] Processing aid: 1 part (stearic acid)

[0065] Ultra-fine carbon material: 2 parts (graphene)

[0066] Tea polyphenols: 1 part

[0067] Preparation method:

[0068] Pretreatment: At 80 °C, mix 12 parts of brucite powder with 1.2 parts of silane coupling agent KH-550, and stir with a high-speed mixer for 20 minutes to ensure uniform coating.

[0069] Pre-dispersion: In a ball mill, ball mill 4 parts of ammonium polyphosphate and 4 parts of melamine polyphosphate until the particle size is less than 5 μm, add 2 parts of zinc borate and continue ball milling to form uniform composite particles, and make a slurry with liquid paraffin in a ratio of 1:0.5.

[0070] Staged kneading:

[0071] The first stage: Plasticate nitrile rubber in a Banbury mixer at 120 °C for 3 minutes.

[0072] The second stage: Add pre-dispersed phosphorus-nitrogen compound flame retardant and carbon black, and mix at 135 °C for 5 minutes.

[0073] The third stage: Add the remaining raw materials and mix at 125 °C for 4 minutes.

[0074] Vulcanization and molding: Mold and vulcanize the mixed rubber at 160 °C and a pressure of 12 MPa. The vulcanization time is 1.5 minutes per millimeter of thickness.

[0075] Example 2: Formula:

[0076] Nitrile rubber: 90 parts

[0077] Aluminum hydroxide: 20 parts

[0078] Hydrotalcite powder: 10 parts

[0079] Phosphorus-nitrogen compound flame retardant: 10 parts

[0080] Zinc borate: 3 parts

[0081] Carbon black: 20 parts

[0082] Vulcanization system: 4 parts

[0083] Processing aid: 2 parts

[0084] Ultra-fine carbon material: 1 part

[0085] Tea polyphenols: 2 parts

[0086] Preparation method: Pretreatment: At 100 °C, mix 10 parts of hydrotalcite powder with 0.5 part of silane coupling agent KH-550, and stir with a high-speed mixer for 20 minutes.

[0087] Pre-dispersion: In a ball mill, ball mill 5 parts of ammonium polyphosphate and 5 parts of melamine polyphosphate until the particle size is less than 5 μm, add 3 parts of zinc borate and continue ball milling to form uniform composite particles, and make a slurry with liquid paraffin in a ratio of 1:0.5.

[0088] Segmented mixing:

[0089] The first stage: Plasticate nitrile rubber in a Banbury mixer at 125 °C for 4 minutes.

[0090] The second stage: Add pre-dispersed phosphorus-nitrogen compound flame retardant and carbon black, and mix at 140 °C for 5 minutes.

[0091] The third stage: Add the remaining raw materials and mix at 130 °C for 4 minutes.

[0092] Vulcanization molding: The mixed rubber is molded and vulcanized under a pressure of 15 MPa at 165 °C, and the vulcanization time is 1.8 minutes per millimeter of thickness.

[0093] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A fireproof and flame-retardant rubber connector, characterized in that: It includes the following components by weight parts: 90-100 parts of nitrile rubber, 20-30 parts of aluminum hydroxide, 10-15 parts of brucite powder, 10-12 parts of phosphorus-nitrogen compound flame retardant, 2-5 parts of zinc borate, 10-20 parts of carbon black, 3-6 parts of vulcanization system, 1-2 parts of processing aid, 1-3 parts of ultrafine carbon material, and 1-2 parts of tea polyphenols.

2. The fireproof and flame-retardant rubber connector according to claim 1, characterized in that: The phosphorus-nitrogen compound flame retardant is a compound of ammonium polyphosphate and melamine polyphosphate, and the mass ratio of ammonium polyphosphate to melamine polyphosphate is 2:

1.

3. A fireproof and flame-retardant rubber connector according to claim 2, characterized in that: The brucite powder has been surface modified, and the modifier is silane coupling agent KH-550, and the addition amount of the modifier is 1-3% of the mass of the brucite powder.

4. A fireproof and flame-retardant rubber connection according to claim 1, characterized in that: The vulcanization system consists of sulfur, zinc oxide and accelerator DM, and the mass ratio of sulfur, zinc oxide and accelerator DM is 2:5:

2.

5. A fireproof and flame-retardant rubber connection according to claim 1, characterized in that: The particle diameter of the zinc borate is less than 5 microns, the ultrafine carbon material is graphene, and the processing aid is stearic acid.

6. A preparation method of the fireproof and flame-retardant rubber connector according to any one of claims 1-5, characterized in that It includes the following steps: Pretreatment: Under the condition of 80-100 °C, 15 parts of brucite powder and 1.5 parts of silane coupling agent KH-550 are mixed, and high-speed stirring is used for mixing for 20 minutes to ensure that the silane is evenly coated on the surface of the brucite powder to improve its compatibility with the rubber matrix; Predispersion: Weigh 6 parts of ammonium polyphosphate and 6 parts of melamine polyphosphate, and ball mill them in a ball mill to ensure that their particle size is less than 5 μm. After the ball milling is completed, 5 parts of zinc borate are added to the mixture, and ball milling is continued until fully mixed to form uniform composite particles, and a slurry is made with liquid paraffin according to a mass ratio of 1:0.5; Segmented mixing: The first stage: The nitrile rubber is plastified in a Banbury mixer at 120-125 °C for 2-4 minutes; The second stage: Add 50-60% of the phosphorus-nitrogen compound flame retardant and carbon black, and mix at 130-140 °C for 4-6 minutes; The third stage: Add the remaining raw materials and mix at 120-130 °C for 3-5 minutes; Vulcanization and molding: The mixed rubber is molded and vulcanized by compression molding at 150-165 °C and 12-18 MPa pressure, and the vulcanization time is calculated at 1.2-1.8 minutes per millimeter of the product thickness.

7. The preparation method of a fireproof and flame-retardant rubber connector according to claim 6, characterized in that: During the segmented mixing process, the mixing temperature in the second stage is 5-15 °C higher than that in the third stage.

8. The preparation method of a fireproof and flame-retardant rubber connector according to claim 6, characterized in that: Add a smoke suppressant accounting for 0.5-1.5% of the total mass of the rubber in the third stage of the segmented mixing. The smoke suppressant is a compound of ferrocene and ammonium molybdate, and the mass ratio is (2:1)-(1:1).

9. The preparation method of a fireproof and flame-retardant rubber connector according to claim 7, characterized in that: The vulcanization time is calculated at 1.5 minutes per millimeter of the product thickness.

10. The preparation method of a fireproof and flame-retardant rubber connector according to claim 8, characterized in that: The smoke suppressant is a compound of ferrocene and ammonium molybdate, and the mass ratio is 2:1.

Citation Information

Patent Citations

  • High-flame retardant rubber material in extrusion molding and preparation method thereof

    CN103146081A

  • Master batch, rubber material and preparation method and application thereof

    CN116355294A

  • Flame-retardant functionalized graphene modified nitrile rubber and preparation method thereof

    CN119320520A

  • Composite flame retardant, flame-retardant vibration-damping rubber with excellent comprehensive performance, and preparation methods thereof

    EP4083132A1